SISTEM PALANG PINTU PERLINTASAN KERETA API OTOMATIS DENGAN KOMUNIKASI WIRELESS BERBASIS ARDUINO - Medilla Kusriyanto; Nendy Wismoyo (Teknoin, 2017)
Trains are a means of transportation of interest to the public in Indonesia. In addition to fast, the cost and convenience of service on the train became one of the reasons for the selection of this transportation. Accidents at railway crossings are common in Indonesia. One reason is the absence of a doorstop in the railway crossing. In this research, we try to develop the closing and opening tool of train railway crossing automatically. This device is equipped with vibration sensor and infrared sensor to detect train arrival. The sensor readout signal will be processed by arduino UNO and sent to the control center using wireless nRF24l01 + PA + LNA module. The signal will be received by the control module using the same receiver module and will be processed by arduino mega 2560 to open and close the railway crossing door equipped with LED indicator. Based on the test results, the nRF24l01 + PA + LNA transceiver module can work at a distance of 940 meters with an average data transmission delay of 1.2952 seconds.